Bonding mechanism and interface characterisation during dissimilar friction stir welding of an aluminium/polymer bi-material joint. (3rd April 2017) - Khodabakhshi, F.; Haghshenas, M.; Chen, J.; Shalchi Amirkhiz, B.; Li, J.; Gerlich, A.P.
Abstract : In the present study, detailed microstructural characterisation of a friction-stir-welded joint between AA5059 alloy and high-density polyethylene was carried out using field-emission scanning and high-resolution-transmission electron microscopy analysis. The structural features indicate large numbers of macro-, micro- and nano-mechanical interlocks between the Al-fragments and melted/re-solidified polymer matrix at the stir zone of the joint, with a 30-nm thick semi-crystalline aluminium structure layer elevated in levels of O, and traces of C at the interface. An ultrafine-grained structure with an average cell size of <100 nm was formed for the embedded Al-alloy fragments in the polymer matrix, as a result of low-temperature severe plastic deformation during friction-stir welding process. The interfacial chemical reactions assisted by generation of nano-scale pores inside the metal surface at the interface and secondary Van der Waals bonding are suggested as the main joining mechanisms, leading to significant improvements in the mechanical properties.